NILAI MORAL DALAM CERITA RAKYAT MASYARAKAT DAYAK BAKATI RIUK DI DESA SANGO KABUPATEN BENGKAYANG - Era Fazira; Martono Martono; Antonius Totok Priyadi (Universitas Tanjungpura, 2021)
AbstractDescription of moral values in the folklore of the Dayak Bakati Riuk community in Sango Village, Bengkayang Regency. The method used is descriptive. The form of research is qualitative. The meaning of the data in this research is folklore told by informants in Sango Village, Bengkayang Regency. Data collection techniques by means of observation techniques, interview techniques, recording techniques, and recording techniques. Based on the overall data, the folklore of the Dayak Talenti Riuk community in Sango Village which was analyzed amounted to 31 data. This research is related to the 2013 curriculum for Indonesian language subjects in class X SMA in odd semesters which is proposed as a reference material (folklore) for teaching and learning activities in schools.Keywords: Oral literature, Moral Values, Folklore